Analisis Daya Saing, Dinamika, dan Determinan Penawaran Ekspor Komoditas Unggulan Indonesia ke United Kingdom: Institut Pertanian Bogor - Fasya Miftah Akbar; Widyastutik (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2022)
The United Kingdom is an industrial and developed country that has the potential to become Indonesia's leading commodity export market. This study aims to analyze the competitiveness, dynamics, and determinants of Indonesia's superior commodity export offerings to the United Kingdom. This research method uses qualitative and quantitative approaches with RCA, EPD, x-model, and panel data regression analysis. There are ten main export commodities that have the highest RCA which is analyzed for their position and market development. So it was found that there were eight commodities that were in a falling star position with potential market development and two commodities were in a retreat position with less potential market development. The results of regression estimates show that real GDP per capita of Indonesia, export prices, population growth of Indonesia, and RCA have a significant effect on the value of Indonesian main export commodities to United Kingdom. Meanwhile, real GDP per capita of United Kingdom, economic distance and population growth of United Kingdom have no significant effect on the value of Indonesian main export commodities to United Kingdom.